Molecular Modeling of Ionic Liquids: Force‐Field Validation and Thermodynamic Perspective from Large‐Scale Fast‐Growth Solvation Free Energy Calculations. Issue 9 (30th June 2022) - Sun, Zhaoxi; Wang, Mao; He, Qiaole; Liu, Zhirong
Abstract: In molecular modelling of novel solvents such as ionic liquids, it is common to scale atomic charges to improve the experiment‐simulation agreement for some selected properties. As these liquids are designed to solvate solutes, whether the solvation thermodynamics could be correctly described is of utmost importance. Therefore, we present a comprehensive large‐scale calculation of solvation free energies via nonequilibrium fast‐switching simulations for a spectrum of molecules in ionic liquids, the atomic charges of which are scaled to maximize the prediction‐experiment correlation. Further, the density‐derived choice is compared with the solvation‐thermodynamics‐derived one. When the scaling factor is decreased, the density exhibits a monotonically decreasing behavior due to weaker inter‐molecular interactions produced by scaled atomic charges. However, solvation free energies do not show consistent monotonic behaviors, which are caused by competing electrostatic and vdW responses to the scaling‐parameter variation. More intriguingly, the solvation‐free‐energy‐derived scaling factor is generally slightly higher than the density‐derived one. We further calculate partition coefficients ortransfer free energies of solutes from water to ionic liquids to provide another thermodynamic perspective of charge scaling. Another central result is the detailed evaluation of the widely used force fields for bonded and vdW terms, i.e., the GAFF derivatives. Abstract : Large‐scale molecular simulations are performed to estimate the mass density of ionic liquids and solvation and water‐ionic‐liquids transfer free energies. Disparate electrostatic and vdW responses to charge scaling are observed. The best scaling parameter from solvation thermodynamics is generally 0.1 larger than that from mass density. The general AMBER force field derivatives are also refitted to assess their suitability for ionic‐liquids derivatives.